Sociolinguistics Analysis Of Register Used In Soccer Page Of Social Media Facebook - Rahmawati, Alis, Dr. Maryadi, M.A, Siti Zurhriah Ariatmi, M. Hum (2014)
This research paper aims to describe the linguistics form and the meaning of register used in soccer page of social media facebook. Soccer page is a space where news about soccer is shared. This page is handled by maintenance who always post updated news about soccer, such as score updates, news of last match, and news of the player or the specific club. There are many new words created in soccer pages. The type of research is descriptive qualitative. The object of this research is the register used in soccer page of social media facebook. The data are register words and phrases included in printed material used in soccer page of social media facebook. The data source is the post in soccer page of social media facebook. The writer collects the post in soccer page, reads the post thoroughly, and writes down the register words and phrases, and gives the code of the data. In analyzing the data, the writer classifies the data into categories as the register, analyzes the data by identifying the linguistic form of the register, analyzing the context of situation of the data based on Halliday's theory, Identifying the differences between lexical and contextual meaning based on Larson's theory. Based on the analysis, the researcher finds there are 13 data of noun, 1 datum of verb, 1 datum of adjective, 15 data of compound word, 1 datum of abbreviation, and 6 data of noun phraseand there are two types of meaning: 9 data of lexical meaning and 28 data of contextual meaning. This means that the highestfrequency data of linguistic form are in compound word (40.5%) and meaning are in contextual meaning (75.6%).